#TITLE_ALTERNATIVE# - (NIM 15105009); Pembimbing: Dr. Ir. S.Hendriatiningsih, MS., dan Dr. Deni Suwardhi, ST., JANANURAGADI
The more rapid advancement of technology in progress measurement result based mapping three-dimensional (3D). One use of 3D-based mapping is to reconstruct a building object. The instrument used to perform 3D mapping is based on Image Station and Terrestrial Laser Scanner. Buildings to be reconstructed object model is Cangkuang Temple. Measurements with both devices, which are Terrestrial Laser Scanner and Image Station conducted to determine the quality of data from each instrument. By selecting points from each herd size data, data quality will be obtained from each instrument by measuring the distance and angle from the herd point. Moreover, it can be made 3D models surface using by software. Based on the analysis of measurement results using a second instrument, the difference in the density of point cloud resulting in highly significant differences in the 3D model and 3D model surface. There is a difference in the yield of the transformation by using both these tools.